GE_GERICHTE C/3695/2015 vom 20. Februar 2018 - GE Cour de justice (2018)
ACTION EN CONTESTATION DE L'ÉTAT DE COLLOCATION ; MOTIVATION ; IMPUTATION ; ACOMPTE | CO.85.al1; CO.87.al1; CPC.308.al2; CPC.311.al1